Constitutive activation of S1P receptors at the trans-Golgi network is required for surface transport carrier formation - Okada, Taro; Nishida, Susumu; Zhang, Lifang; Ibrahim Mohamed, Nesma Nabil; Wang, Tianyou; Ijuin, Takeshi; Kajimoto, Taketoshi; Nakamura, Shun-Ichi (iScience, 2021)
The importance of the G-protein βγ subunits in the regulation of cargo transport from the trans-Golgi network (TGN) to the plasma membrane (PM) is well accepted; however, the molecular mechanism underlying the G-protein activation at the TGN remains unclear. We show here that sphingosine 1-phosphate (S1P) receptors at the PM were trafficked to the TGN in response to a surface transport cargo, temperature-sensitive vesicular stomatitis virus glycoprotein tagged with green fluorescent protein accumulation in the Golgi. The receptor internalization occurred in an S1P-independent manner but required phosphorylation by G-protein receptor kinase 2 and β-arrestin association before internalization. Continuously activated S1P receptors in a manner dependent on S1P at the TGN kept transmitting G-protein signals including the βγ subunits supply necessary for transport carrier formation at the TGN destined for the PM. [Display omitted] •S1P receptors traffic from the PM to Golgi in a surface cargo-dependent manner•S1PR trafficking follows GRK2-dependent phosphorylation and β-arrestin binding•S1PRs at the Golgi are continuously activated by S1P while sending G-protein signals•S1PR/Gβγ signals at the Golgi are indispensable for surface transport carrier formation Cell biology; Organizational aspects of cell biology; Functional aspects of cell biology